2008
DOI: 10.1016/j.drugalcdep.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental lead exposure alters methamphetamine self-administration in the male rat: Acquisition and reinstatement

Abstract: The rate of acquisition of drug self-administration and the return to drug seeking are important elements of the overall drug profile, and are essential factors in understanding risks associated with drug abuse. Experiment 1 examined the effects of perinatal (gestation/lactation) lead exposure on adult rates of acquisition of intravenous (i.v.) methamphetamine self-administration. Experiment 2 investigated the effects of perinatal lead exposure on drug-maintained responding in a reinstatement (relapse) paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Rocha et al (2008) found that rats exposed developmentally to the identical lead treatment employed here were slower to acquire self-administration responding for a .02 mg/kg methamphetamine infusion than their control counterparts. Moreover, similarly exposed animals were less likely than controls to reinstate responding in an extinction context when administered a drug (methamphetamine [i.p.])…”
Section: Discussionmentioning
confidence: 58%
“…Rocha et al (2008) found that rats exposed developmentally to the identical lead treatment employed here were slower to acquire self-administration responding for a .02 mg/kg methamphetamine infusion than their control counterparts. Moreover, similarly exposed animals were less likely than controls to reinstate responding in an extinction context when administered a drug (methamphetamine [i.p.])…”
Section: Discussionmentioning
confidence: 58%
“…K. Miller, Nation, & Bratton, 2000, 2001; Nation, Miller, & Bratton, 2000), cadmium (Nation & Miller, 1999), manganese (Guilarte et al, 2008; McDougall et al, 2008; Reichel et al, 2006), and methylmercury (Eccles & Annau, 1982; Newland, Reed, & Rasmussen, 2015; Rasmussen & Newland, 2001; Reed et al, 2008; Wagner, Reuhl, Ming, & Halladay, 2007) alter dopamine neurotransmission and alter the response to experimenter -administered psychostimulants during adulthood, often in a sex-specific manner. This is the first study to demonstrate that rats perinatally exposed to PCBs exhibit differences in the propensity to acquire self -administration of cocaine and is one of a handful of other studies demonstrating monoamine-disrupting environmental contaminants such as lead (Nation, Cardon, Heard, Valles, & Bratton, 2003; Nation, Smith, & Bratton, 2004; Rocha, Valles, Bratton, & Nation, 2008; Rocha, Valles, Cardon, Bratton, & Nation, 2005; Rocha, Valles, Hart, Bratton, & Nation, 2008; Valles, Rocha, Cardon, Bratton, & Nation, 2005) and cadmium (Cardon, Rocha, Valles, Bratton, & Nation, 2004) can also alter psychostimulant self-administration in adulthood after perinatal exposure. Thus, there is converging research to demonstrate that exposure to monoamine-disrupting chemicals during early development can promote drug-seeking later in life.…”
Section: Discussionmentioning
confidence: 82%
“…In adult animals, previous gestational and lactational exposure to lead produced an increase in the sensitivity to cocaine as exhibited by faster acquisition of self-administration behavior [42], maintenance of self-administration at doses lower than non-exposed controls [32], a higher vulnerability to relapse [30], and an increase in the motor stimulating effects [31]. For methamphetamine, on the other hand, previous gestational and lactational exposure to lead resulted in reduced self-administration acquisition [43], self-administration at doses higher than non-exposed controls [41], and a decreased vulnerability to relapse [43] in adult animals. The motor stimulating effects of methamphetamine were enhanced in adult animals that had perinatal lead exposure, but the effects were only observed during early testing days with controls showing similar levels by later testing days [6].…”
Section: 0 Discussionmentioning
confidence: 99%